2021
DOI: 10.1371/journal.pone.0244599
|View full text |Cite|
|
Sign up to set email alerts
|

Hurricane impacts on a coral reef soundscape

Abstract: Soundscape ecology is an emerging field in both terrestrial and aquatic ecosystems, and provides a powerful approach for assessing habitat quality and the ecological response of sound-producing species to natural and anthropogenic perturbations. Little is known of how underwater soundscapes respond during and after severe episodic disturbances, such as hurricanes. This study addresses the impacts of Hurricane Irma on the coral reef soundscape at two spur-and-groove fore-reef sites within the Florida Keys USA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 137 publications
0
10
0
Order By: Relevance
“…Both sites yielded the lowest coverage in the encrusting zoanthid (P. caribaeorum), yet differed in dominant coral taxa and protection level, suggesting that these sites may possess strong fine-scale habitat traits or biological legacies from previous disturbance impacts for certain coral taxa [93][94][95][96]. For example, following Hurricane Irma's direct impact on the study sites, the coral reef soundscape at ESB during the same sampling periods (2017-2018) showed signs of recovery within weeks to months following the disturbance through the return of periodic fish chorusing and snapping shrimp activity [97]. NOAA's National Weather Service has recorded ten tropical storms and nine hurricanes either passing over or making landfall in the Florida Keys and the Dry Tortugas between 2000 and 2020 [98].…”
Section: Discussionmentioning
confidence: 97%
“…Both sites yielded the lowest coverage in the encrusting zoanthid (P. caribaeorum), yet differed in dominant coral taxa and protection level, suggesting that these sites may possess strong fine-scale habitat traits or biological legacies from previous disturbance impacts for certain coral taxa [93][94][95][96]. For example, following Hurricane Irma's direct impact on the study sites, the coral reef soundscape at ESB during the same sampling periods (2017-2018) showed signs of recovery within weeks to months following the disturbance through the return of periodic fish chorusing and snapping shrimp activity [97]. NOAA's National Weather Service has recorded ten tropical storms and nine hurricanes either passing over or making landfall in the Florida Keys and the Dry Tortugas between 2000 and 2020 [98].…”
Section: Discussionmentioning
confidence: 97%
“…Acoustic monitoring thus provides an opportunity to overcome many of the challenges associated with studying extreme weather events, by allowing pre- and post-typhoon comparisons (Altwegg et al, 2017; Rajan et al, 2022), and capturing ecological responses to typhoons across scales in space and time (Lin et al, 2020) using a multidimensional stability framework (Donohue et al, 2013). Of the few studies that have used acoustic monitoring to capture storms or extreme events, most focused on marine soundscapes (Boyd et al, 2021; Locascio & Mann, 2005; Simmons et al, 2021), though Gottesman et al . (2021) recently showed that terrestrial soundscapes were less resistant than those of coral reefs to hurricane disturbance.…”
Section: Introductionmentioning
confidence: 99%
“…Acoustic monitoring thus provides an opportunity to overcome many of the challenges associated with studying extreme weather events, by allowing preand post-typhoon comparisons (Altwegg et al, 2017;Rajan et al, 2022), and capturing ecological responses to typhoons across scales in space and time (Lin et al, 2020) using a multidimensional stability framework (Donohue et al, 2013). Of the few studies that have used acoustic monitoring to capture storms or extreme events, most focused on marine soundscapes (Boyd et al, 2021;Locascio & Mann, 2005;Simmons et al, 2021), though Gottesman et al (2021) recently showed that terrestrial soundscapes were less resistant than those of coral reefs to hurricane disturbance. Embedded within terrestrial soundscapes, bird vocalisations provide the opportunity to assess the impact of typhoons on critical indicator taxa (Gasc et al, 2017), while acoustic indices provide rapid information on a combination of biodiversity and other meaningful aspects of soundscape change (Bradfer-Lawrence et al, 2020;Harris et al, 2016;Rajan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Sounds are ubiquitous in coral reef ecosystems, where many reef-associated animals intentionally or unintentionally produce sounds (Mooney et al, 2020). In addition, geophysical events (e.g., wind, waves, and rain) and anthropogenic activities (e.g., shipping, fishing, and scuba diving) generate perceptible sounds (Lin et al, 2021;Simmons et al, 2021). Listening to underwater soundscapes-the mixture of biophony, geophony, and anthropophonyopens a new avenue for studying the ecological and human dimensions of coral reef ecosystems (Figure 1).…”
mentioning
confidence: 99%